“A UMBANDA TEM FUNDAMENTO E É PRECISO PREPARAR”: O PAPEL DA EDUCAÇÃO A DISTÂNCIA PARA O CONHECIMENTO SOBRE A UMBANDA - Fernandes, Stéfani Martins (2019)
The teaching of Umbanda, aiming not to be approached in regular educational spaces, ended, for many decades restricted to the terreiros and to the adherents of the religion. Since the beginning of the 2000s, some supporters and leaders of Umbanda have carried out projects to disseminate religion through teaching practices, both in nonformal and non-formal non-formal spaces, through websites. These institutions ended up covering those interested in knowing Umbanda, not only practitioners - mediums - or leaders of terreiros. In the accomplishment of the present research, it was tried to answer the following question: what is the role of the distance courses for the knowledge about Umbanda? The objective of this study is to analyze the role of distance learning courses for knowledge about Umbanda. In relation to the proposed objective, four specific objectives were chosen, namely: to understand how the formation and relationship of the tutors in the courses of the site Umbanda EAD; investigate how learning is understood and processed through the Umbanda EAD website; to perceive what has changed - or not - in the participants' thoughts on Umbanda after joining these courses and to reflect on the possible contributions of Umbanda teaching to reduce religious intolerance. In this sense, a qualitative methodology was chosen, through the case study approach, based on the references of Robert Yin (2015). To cover the objectives proposed in this research, interviews - involving a tutor and one of the creators of the Umbanda EAD site - and questionnaires - were used for the participants of the courses. These methodologies were planned and executed according to studies by Robert Yin (2015) and Maria Michel (2015). For a better interpretation of the information obtained, the analysis of the data was made through the Content Analysis proposed by Bardin (2007). Finally, based on the data obtained, the relevance of distance learning about Umbanda was perceived for the understanding and dialogue about it, aiming at the emancipation of its practice. In addition, it was intended, with this research, to contribute to the decrease of the prejudices about the Umbanda and to cooperate with the research on the field of the Science of Religions, on Umbanda and its teaching.